PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN SEMAI TANJUNG (Mimusops elengi L.) - Syaripah Ainiah; Sulaiman Bakri; Muhammad Muchtar Effendy (Universitas Lambung Mangkurat, 2020)
The use of good planting media is that it can hold water and air in comparable and sufficient amounts, free of pests and diseases, many contain nutrients. The cape plant (M .elengi L.) has high resistance and absorption to contaminate cement dust and can produce a fragrant odor that can neutralize the stench. The purpose of this study was to determine the effect of the composition of growing media on the growth of tanjung seedlings (M. elengi L.) and compare the growth of tanjung seedlings (M. elengi L.) in the treatment with 100% topsoil planting media composition, topsoil and peat soil, topsoil and charcoal rice husk and topsoil and cocopeat. This study uses a Completely Randomized Design (CRD) method which consists of 4 treatments and repetitions 10 times, thus obtaining 40 experimental plants. Media composition consisting of 4 treatments namely topsoil 100%, topsoil and peat soil (1: 1) topsoil and rice husk charcoal (1: 1) topsoil and cocopeat (1: 1). The composition of the planting medium tested significantly affected the growth of tanjung (M. elengi L.) seedlings on height and number of leaves due to Fcount was greater than Ftable while the increase in diameter did not have a significant effect because Fcount was smaller than Ftable. The growth of tanjung seedlings (M. elengi L.) in each treatment composition of different planting media is known that the treatment with media top soil and rice husk charcoal showed a high increase of 9.35 cm, number of leaves of 11.7 strands and diameter of 0, 21 mm larger than treatment K (topsoil 100%), treatment A (topsoil and peat soil) and treatment C (topsoil and cocopeat).Keywords: Tanjung; seedlings; growth; composition of planting media